Estudio de viabilidad para la creación de un centro estético para animales de compañía en la ciudad de Chone - Vera Acosta, María Belén (2025)
The purpose of this study was to analyze the feasibility for the establishment of an aesthetic center for pets in Chone city, Ecuador. The methodology adopted involved a qualitative approach, through the implementation of surveys to 67 canine tutors in the locality, which facilitated the collection of meaningful data about their preferences and consumption patterns. The results evidenced a significant lack of specialized aesthetic services for animals in Chone, despite the increase in the pet population and the global trend of humanizing companion animals. Furthermore, the findings indicate that 99% of the survey participants show interest in using a new aesthetic center, while 97% recognize the importance of canine aesthetic services and would be willing to pay a high cost for high-quality services. In terms of economic viability, opportunities were identified to generate employment, strengthen the local economy, and establish a sustainable business model. The statistical analysis confirms significant relationships (p<0.001) between the variables under study. These results suggest a clear business opportunity in the sector, demonstrating the determination of clients who are ready for the establishment of a specialized aesthetic center in Chone, with considerable profit potential. These results suggest a clear business opportunity in the sector, demonstrating the determination of clients who are ready for the establishment of a specialized aesthetic center in Chone, with considerable profit potential.